Calcidiol Involvement in Hypertension in Pregnancy - Pratama Putra, Bayu; Sunarno, Isharyah; Mailoa, Johnsen; Lukas, Efendi; Sriwijaya (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the relationship of vitamin D levels with severe preeclampsia, chronic hypertension in pregnancy, and HELLP syndrome. A comparative analytic cross-sectional study on 91 participants. Data and blood samples were taken from all pregnant women with significant months of pregnancy diagnosed with severe preeclampsia, chronic hypertension, and HELLP syndrome in educational hospitals. Statistical analysis was performed using Chi Square and one-way ANOVA. From a total of 91 participants, there were 18 HELLP syndromes, 11 chronic hypertensions, and 62 with severe preeclampsia. Demographic data and vitamin D levels among groups were compared, and association analyses were performed. There were no statistically significant differences in age, parity, gestational age, pre-pregnancy BMI, or weight gain during pregnancy between these groups. The levels of SGOT, SGPT, creatinine, and urea in patients with HELLP syndrome were higher, whereas platelet counts were lower than the 2 other groups (p <0.001). No differences or associations were found between vitamin D levels in severe preeclampsia, HELLP syndrome, and chronic hypertension in pregnancy. Vitamin D is involved in the pathogenesis of hypertension in pregnancy, with the finding of lower levels in chronic hypertension compared with levels in severe preeclampsia and HELLP syndrome; however, calcidiol is not a factor that is directly involved in the pathomechanism of hypertension in pregnancy.